Ecos das vozes do Sul na escola pública: formação crítica e decolonial de uma professora de inglês de alunos do MST - Redondo, Diego Moreno (Universidade Federal de São Carlos, 2024)
Coloniality, resulting from colonialism, assumes a management and control stance in different areas of society, including schools. Studies reveal that exclusion is a phenomenon caused by society through mechanisms that make students feel excluded and believe that they are in a subordinate position (Leffa, 2007; 2011). Therefore, when it comes to the school institution, faced with knowledge that accentuates coloniality, what would be the possibilities to overcome it? Quijano (1992) proposes some alternatives: freeing oneself from hegemonic knowledge, producing an episteme from the local context; propose decolonial practices that consider the marginalized, that is, the author suggests decoloniality as a proposal to combat coloniality. Given these alternatives, we carried out collaborative action research in order to offer critical-reflective training for the English teacher who teaches MST students at a municipal public elementary school (final years) in the interior of São Paulo. The objective was to hold meetings at HTPC for pedagogical improvement carried out in reflective sessions that addressed classroom dilemmas, aiming at an inclusive and decolonial practice, contemplating the “Voices of the South”, that is, students who are on the margins in English classes for showing behavior of not belonging to the group of foreign language learners for feeling in a position of inferiority and inequality arising from the exclusion mechanisms caused by society. As it is a collaborative action research, the study was organized into three stages: 1- pre-intervention observation; 2- intervention; 3- pos-intervention observation. Observations of PC classes brought us input for discussions in reflective sessions; the intervention was carried out in critical-reflective training with the collaborating teacher and with the interdisciplinary project with the students. Post-intervention observation revealed the impacts of working with research participants. Critical reflective training was carried out as a strategy for professional improvement based on the educational perspective of critical literacy, with the objective of developing a decolonial stance. The research confirmed hypotheses that there are different factors that contribute to colonial teaching, such as, for example, the teacher’s practice, teaching material, the school environment, curricular parameters, among others. Therefore, the research results revealed that there was a deconstruction of hegemonic and colonial discourses in the school environment. Furthermore, there was a significant transformation in teaching practice, aiming at a liberating, dialogical and decolonial education. A considerable change in the behavior of participating students was also observed, as they showed interest and a desire to be part of a group of foreign language learners, which did not happen before the intervention. In this way, the research achieved its objectives, using critical-reflective training as a strategy for the benefit of a decolonial education.
Echoes of voices from the South in public schools: critical and decolonial formation of an english teacher of MST students
Keywords: Ensino-aprendizagem de inglês; Alunos do MST; Escola pública; Justiça social; Formação crítico-reflexiva; Decolonialidade; English Teaching-learning; MST students; Social justice; Public school; Critical-reflective training; Decoloniality; Critical literacy; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA